IMPLEMENTATION OF TAHFIDZUL QUR'AN LEARNING FOR STUDENTS OF PKPU NEUHEUN MIDDLE SCHOOL ACEH BESAR DISTRICT - Jamaluddin, Jamaluddin; Isa, M.; Quthni, Addar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Implementation of Tahfidzul Qur’an learning at PKPU Neuheun Middle School need done optimization on several aspects, such as management time and improvement support family, for reach more results​ maximum in increase memorization students. Type of research use approach qualitative with type study field research. Research results shows that 1). Implementation method Tahfidzul Qur’an learning at PKPU Neuheun Middle School Aceh Besar District is that method talaqqi and muraja'ah applied in a way effective, with competent teacher guidance and environment supportive schools. Although​ there is constraint like difference ability students and limitations time, this program in a way overall walk good and giving impact positive on memorization students, although Still need improvement in support family and management time learning. 2). Supporting and inhibiting factors in implementation Tahfidzul Qur’an learning at PKPU Neuheun Middle School Aceh Besar District is that the success of this program supported by teacher competence, methods learning effective like talaqqi and muraja'ah, as well as environment conducive Islamic schools. On the other hand, the challenges main issues faced is difference ability memorize students, lack of support family, limitations time learning, and limited facilities. Management and improvement to factors This required for optimize results learning tahfidz at school.